Analysis of Gene Expression Profiles, Cytokines, and Bacterial Loads Relevant to Alcoholic Liver Disease Mice Infected With V. vulnificus - Feng, Zi-Han; Li, Shi-Qing; Zhang, Jia-Xin; Ni, Bin; Bai, Xin-Ru; Xu, Jian-Hao; Liu, Zhen-Bo; Xin, Wen-Wen; Kang, Lin; Gao, Shan; Wang, Jing; Li, Yan-Wei; et al. (Frontiers in Immunology, 2021)
Patients with liver disease are susceptible to infection with Vibrio vulnificus (V. vulnificus), but the specific reasons remain elusive. Through RNA-seq, we found that when mice with alcoholic liver disease (ALD) were infected with V. vulnificus by gavage, compared with the Pair group, the small intestinal genes affecting intestinal permeability were up-regulated; and the number of differentially expressed genes related to immune functions (e.g., such as cell chemotaxis, leukocyte differentiation, neutrophil degranulation.) decreased in the liver, spleen and blood. Further analysis showed that the number of white blood cells decreased in the Pair group, whereas those in the ALD mice did not change significantly. Interestingly, the blood bacterial load in the ALD mice was about 100 times higher than that of the Pair group. After the ALD mice were infected with V. vulnificus, the concentrations of T cell proliferation-promoting cytokines (IL-2, IL-23) decreased. Therefore, unlike the Pair group, ALD mice had weaker immune responses, lower T cell proliferation-promoting cytokines and higher bacterial loads post-infection, possibly increasing their susceptibility to V. vulnificus infection. These new findings we presented here may help to advance current understanding of the reasons why patients with liver disease are susceptible to V. vulnificus infection and provides potential targets for further investigation in the context of treatment options for V. vulnificus sepsis in liver disease patient.